Credit Union-based Democracy at the Border of Indonesia in the Global Economic Era - Elyta, Elyta; Zulkarnaen, Zulkarnaen; Herlan, Herlan (Jurnal Politik Indonesia: Indonesian Political Science Review, 2020)
This research was conducted to design a Credit Union (CU) based democracy model at the Indonesia border especially the Sajingan Besar border facing the global economic era. This was done as an effort to improve the economy and minimize poverty. This study's location is in the border area of Sambas Regency to be precise in Sajingan Besar District because it is directly adjacent to the neighboring country so that it is a specific area. Still, the city is included in the underdeveloped category. Previous research that has been researched previously examined the importance of having women join CU business institutions using the perspective of women's emancipation in West Kalimantan. There is a novelty in this research, namely, discussing it from deliberative-participatory democracy based on CU at the border in the global economic era. Methods of data collection in this study using interview techniques, observation, and study documentation. Informants were determined using a purposive technique. Based on these techniques, the informants in this study were the Head of the Sajingan Besar sub-district, community leaders, youth leaders, administrators of CU Bonaventura, members of CU Bonaventura, and Chairman of the West Kalimantan Border Forum. The analysis used is using qualitative analysis. The study results found that to minimize poverty that occurs in border area communities, it is necessary to implement democracy based on CU as an effort to improve the community's economy in the era of the global economy by utilizing natural resources. This CU-based deliberative-participatory democracy is proven through deliberation and participation by members who prioritize member empowerment and the political inclusion of CU members.